CHARACTERISTICS OF ORGANIZING INCLUSIVE EDUCATION IN PRIMARY EDUCATION - Hamdamova , Nafisa Khayriddinovna (Educational Research in Universal Sciences, 2023)
In this article, children and adolescents in need of special support, who are a part of our society, are given social support, education, vocational training, and a place among healthy children. thoughts and opinions are presented on how to grow up as a person who can take advantage of his abilities and opportunities.